AI Transformations Data Networking and Cybersecurity through Advanced Innovative - Israa Alrikabi (Indonesian Journal Publisher, 2026)
The swift pace of the market transformation of the infrastructure of the data networking has introduced the necessity of having a more sophisticated security system to fight a high sophisticated cyber threat. The digital sphere is being developed, networks are working more than ever, and the Internet of Things (IoT), 5 G networks, and cloud technologies are ever-expanding. Though this expansion amount to more connectivity, it is a massive challenge on the security front with the consideration of sharing sensitive information in regard to the changing cyber-attacks. At the same time, the artificial intelligence (AI) has also been presented as one of the technologies that can revolutionize the data networking and cybersecurity. The possibility to process a large amount of data, predict kernels and make decisions in real time, AI is a valuable asset in the direction of solving the arising issues of network security in the new environment. Whether it is the possibility to be more efficient when it comes to utilizing the bandwidth of the network with intelligent resource distribution, or increase the level of information protection against cyber-attacks, AI is changing the way businesses make their web space safer. Within the framework of this research paper, the empirical research of AI in data networking and cybersecurity has been introduced on the basis of information gathered by the network operators, cybersecurity agencies, and government organizations. The paper will focus on some of the core areas, that is, predictive detection of threats, anomaly detection, and incident response, which is automated. The article relying on statistical modeling, visual data analysis, and case study analysis proves the point that AI proves beneficial in terms of identifying the cyber threats and enhancing the network performance, and is more efficient in coping with the challenges than the classical security solutions. Such results indicate that the efficiency of the operations and threat reduction was raised considerably, which confirms the possibility of the application of AI-based solutions. Such a shift toward proactive and reactive AI-based security is going to be the majority as more complicated network topologies and more advanced cybers threat activities are refined. Since the aim of the paper is to respond to the existing issues and elucidate the way the data networking and cybersecurity will evolve in the future, the paper may be used to display useful information about the way AI would transform the data networking and cybersecurity.